Prevalence of dyslipidaemia and hypertension in diabetic patients at Tygerberg Children’s Hospital - Nuckchedee Dookhony, Luvina Devi (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2022.